2022
DOI: 10.1097/dcr.0000000000002176
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Intensified Infliximab Rescue Therapy for Severe Ulcerative Colitis Does Not Reduce Short-term Colectomy Rates or Increase Postoperative Complications

Abstract: BACKGROUND: Dose-intensified rescue therapy with infliximab for hospitalized patients with ulcerative colitis has become increasingly popular in recent years. However, there is ongoing debate about both the efficacy of these regimens to reduce the rate of colectomy and the associated risks of increased infliximab exposure. OBJECTIVE: The purpose of this study was to compare the colectomy and postoperative complication rates in hospitalized patients with severe ulcerative colitis receiving standard infliximab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Two studies conducted in NA reported an initial maintenance pattern in alignment with FDA label recommendations (5 mg/kg every 8 weeks) in a median of 89% of patients (range 78–100%) [ 124 , 125 , 127 , 173 , 174 ]. Outside of NA, most studies ( N = 8) reported an initial maintenance dose of 5 mg/kg every 8 weeks in a median of 100% of patients (range 68–100%) [ 7 , 123 , 132 , 139 143 , 157 , 175 179 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies conducted in NA reported an initial maintenance pattern in alignment with FDA label recommendations (5 mg/kg every 8 weeks) in a median of 89% of patients (range 78–100%) [ 124 , 125 , 127 , 173 , 174 ]. Outside of NA, most studies ( N = 8) reported an initial maintenance dose of 5 mg/kg every 8 weeks in a median of 100% of patients (range 68–100%) [ 7 , 123 , 132 , 139 143 , 157 , 175 179 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the Editor-We read with interest the article by Kosaraju et al comparing the colectomy and postoperative complication rates in hospitalized patients with acute severe ulcerative colitis (ASUC) receiving standard infliximab (IFX) and dose-intensified regimens. 1 The authors found no significant difference in colectomy rates between the 2 groups, but other studies found a lower rate of colectomy in patients with intensified dosing or high-dose IFX. 2 Furthermore, some expert opinions suggest that high-dose IFX induction is now the preferred schedule of administration for IFX induction therapy in ASUC.…”
mentioning
confidence: 86%
“…We thank Drs Dai and Huang for their insightful commentary on our report of infliximab rescue therapy for acute severe ulcerative colitis (ASUC). 1 Dai and Huang highlight that we rely on an imperfect combination of clinical and patient factors to inform treatment and prognosis in ASUC. We agree that much remains unknown about which therapy, including colectomy, is best.…”
mentioning
confidence: 99%